Startup Funding and Venture Capital: A Bibliometric Analysis of Trends and Concept Evolution - Loso Judijanto (North Press, 2025)
This study presents a bibliometric analysis of the scholarly literature on startup funding and venture capital to uncover the intellectual structure, thematic trends, and evolution of concepts within the field. Drawing from 1,102 Scopus-indexed documents published between 2000 and 2024, the analysis employs VOSviewer to visualize keyword co-occurrence, author collaboration networks, temporal trends, and country-level contributions. Results indicate that core themes such as “venture capital,” “investments,” “startups,” and “entrepreneurship” dominate the literature, while newer topics like “crowdfunding,” “entrepreneurial finance,” and “disruptive innovation” are emerging as areas of interest. Author network analysis highlights key contributors such as Lerner, Gompers, and Kaplan, with the United States leading in publication volume and global collaboration. Overlay and heatmap visualizations reveal a shift from traditional finance-oriented research to more diverse, interdisciplinary topics aligned with technological change and global entrepreneurship. The findings offer valuable insights for academics, investors, and policymakers to better understand the dynamics of startup financing and inform future research directions.